PENGARUH KUALITAS JALAN TERHADAP NILAI LAHAN MENGGUNAKAN UJI MANN WHITNEY - ridayati minggir (Retii, 2019)
Sleman Regency is one of the districts in Yogyakarta which is experiencing rapid urban physical development. This regency has a greater impact than the physical development of urban cities in Yogyakarta compared to other districts in the Yogyakarta region. This affects impact to increase the land value. One factor affecting the value of land in Yogyakarta is the quality of the road leading to the land. Road quality is divided into road classes and types of pavement. This paper is to examine the influence of road quality on the value of land transacted in Ngaglik Sleman sub-district using Mann Whitney test. The results show that the influence of road quality on the value of land transacted in Ngaglik subdistrict of Sleman in 2012 to 2016. It shows that there are significant differences in the median land price between groups of road quality. Next, There are significant differences in the distribution of land price data between road quality groups